The Influence of Project-Based Outdoor Learning Activities on Children’s Independence Development - Abdurakhman, R Nur; Lawej, Abdualaziz Ibrahim; Herlina, Nina (International Journal of Educational Qualitative Quantitative Research, 2022)
Outdoor Learning activities are essential to developing children's abilities. Children's independent development is essential to explore children's abilities. Growth and development are continuous processes from conception to adulthood influenced by intrinsic or environmental factors. Development is an increase in abilities in body structures and functions in a regular and predictable pattern as a result of the maturing process. The purpose of this study was to statistically analyze the effect of project-based outdoor learning activities on children's independent development. The method used in this research is pre-experiment. The types of design used in the research are pre-test-post-test. The population studied is kindergarten children influenced by project-based author learning activities on children's independence. The sampling technique used in this study is total sampling. Research showed that the t-test resulted in 0.000 < 0.05. It shows that using the outdoor learning method for children's developing independence is more significant than before when only using the method of conversing in class. Significantly, project-based outdoor learning affects the growth and development of children's independence aged 5-6 years.